2002
DOI: 10.1016/s0014-5793(02)03158-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of deoxyuridine 5′‐triphosphate nucleotidohydrolase from Trypanosoma cruzi1

Abstract: We report the cloning and kinetic characterization of Trypanosoma cruzi deoxyuridine 5P P-triphosphate nucleotidohydrolase (dUTPase) whose coding sequence was isolated by genetic complementation in Escherichia coli. The deduced amino acid sequence was similar to Leishmania major dUTPase although it exhibits an amino acid insertion which is sensitive to protease inactivation. The catalytically active species of the enzyme is a dimer and a detailed kinetic characterization showed that it is highly speci¢c for dU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Thus, proteins serving DNAprotective functions in T. cruzi are considered potential targets for drug therapy. Two such enzymes encoded by the T. cruzi genome are deoxyuridine pyrophosphatase (TcdUTPase) 5 and uracil-DNA glycosylase (TcUNG) 6 which are both involved in protection against uracil in DNA. The former is responsible for the hydrolysis of dUTP to dUMP and pyrophosphate, and thereby eliminates the triphosphate form of deoxyuridine, and erroneous incorporation of dUMP into DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, proteins serving DNAprotective functions in T. cruzi are considered potential targets for drug therapy. Two such enzymes encoded by the T. cruzi genome are deoxyuridine pyrophosphatase (TcdUTPase) 5 and uracil-DNA glycosylase (TcUNG) 6 which are both involved in protection against uracil in DNA. The former is responsible for the hydrolysis of dUTP to dUMP and pyrophosphate, and thereby eliminates the triphosphate form of deoxyuridine, and erroneous incorporation of dUMP into DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic characterization of these novel forms of dUTPases showed that they accepted either dUDP or dUTP as a substrate, whereas the dUMP product was found to be their potent inhibitor, which clearly indicated the distinct mode of action of these enzymes [88,93]. The first dimer dUTPase structure (Trypanosoma cruzi dUTPase) revealed many structural and mechanistic aspects [94].…”
Section: Dimeric Dutpasementioning
confidence: 99%
“…Data of the multiple-turnover hydrolysis of dUTP by C. jejuni dUTPase was fitted 13.1 T.cruzi [9] dimer 0.5 2. Using dUTP concentrations between 5 and 100 mM, the real K m value obtained was 0.66 mM.…”
Section: Kinetic Characterization and Inhibitionmentioning
confidence: 99%
“…dUTPases are present in a variety of different oligomeric forms: monomeric forms are found in herpes virus [5]; homodimers in the Trypanosomatidae and certain bacteria [6,7]; and homotrimers in bacteria and mammals. The homodimeric enzymes lack sequence and structure conservation with the trimeric group of enzymes [8,9]. Campylobacter jejuni, is a microaerophilic, Gramnegative, flagellate, spiral bacterium closely related to the gastric pathogen Helicobacter pylori.…”
Section: Introductionmentioning
confidence: 99%